2022
DOI: 10.1002/app.52144
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self‐healing investigation of waterborne polyurethane based on reversible covalent bond

Abstract: A series of self-healing waterborne polyurethane (WPU) films utilizing reversible covalent bond acylhydrazones diol (PA) as chain extender were successfully synthesized. The self-healing performance of WPU with different content of chain extender PA has been systemically characterized via cut-and-healing tests and mechanical quantitative evaluation. The film can repair cracks through acylhydrazone exchange reactions within 12 h. When the content of PA is 1.5 wt%, the WPU has the highest self-healing efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
(54 reference statements)
0
19
0
Order By: Relevance
“…[ 35 ] Importantly, no peak was observed at 2260 cm −1 , indicating that –NCO had completely reacted. [ 36–38 ] Figure 2b shows the glass transition temperature of the polymer, which also proved the successful synthesis of the product. The glass transition temperature ( T g ) increases slightly from −113 to −111 °C with increasing TA fraction additionally, this was due to increased hydrogen bonding which hindered the mobility of the elastomer, but the elasticity still maintained a low glass transition temperature which facilitated self‐healing.…”
Section: Resultsmentioning
confidence: 72%
“…[ 35 ] Importantly, no peak was observed at 2260 cm −1 , indicating that –NCO had completely reacted. [ 36–38 ] Figure 2b shows the glass transition temperature of the polymer, which also proved the successful synthesis of the product. The glass transition temperature ( T g ) increases slightly from −113 to −111 °C with increasing TA fraction additionally, this was due to increased hydrogen bonding which hindered the mobility of the elastomer, but the elasticity still maintained a low glass transition temperature which facilitated self‐healing.…”
Section: Resultsmentioning
confidence: 72%
“…The intrinsic self-healing process is generally based on the dissociation and rearrangement of dynamic covalent or non-covalent bonds in materials, which can be spontaneous or driven by external stimuli (heat, light, pH, etc.). Dynamic covalent bonds include Diels–Alder bonds [ 18 , 19 , 20 ], disulfide bonds [ 21 , 22 , 23 ], acyl semicarbazides (ASCZ) [ 24 ], acylhydrazone bonds [ 25 , 26 , 27 ], imine bonds [ 28 , 29 , 30 ], borate ester bonds [ 31 , 32 , 33 ], diselenide bonds [ 34 , 35 , 36 ], etc. Dynamic non-covalent bonds include hydrogen bonds [ 37 , 38 , 39 ], metal–ligand coordination [ 40 , 41 , 42 ], host–guest interactions [ 43 , 44 , 45 ], donor–acceptor interactions [ 46 , 47 , 48 ], ionic bonds [ 49 , 50 , 51 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the introduction of dynamic covalent bonds and/or noncovalent bonds into the thermosetting PU has been employed as a means of imparting a degree of reprocessability. , These bonds enable the cross-linked network structure to rearrange at elevated temperature so that PU displays certain levels of self-healing and malleability. , Owing to their lower bond energies, non-covalent bonds are easier to break and reform than dynamic covalent bonds of higher energies, but PU which rely primarily on non-covalent bonds and have few covalent cross-links usually show inferior mechanical properties to polyurethane vitrimers (PUVs) containing dynamic covalent bonds. , High strength, high toughness, and high dimensional stability are essential for PU materials, especially in high-performance coatings and building materials. Different types of dynamic covalent bonds, such as boronic ester bonds, imine bonds, acylhydrazone bonds, disulfide bonds, etc., have been introduced into the network structures to make PUV repairable and recyclable. Some researchers have demonstrated that carbamate bonds are inherently exchangeable. Yan et al have demonstrated that the interchange reactions of carbamate bonds lead to the topological network structure with rearrangement and, therefore, enable processability and welding performance to PUV …”
Section: Introductionmentioning
confidence: 99%